2012
DOI: 10.1002/cncr.27696
|View full text |Cite
|
Sign up to set email alerts
|

A microRNA expression signature for the prognosis of oropharyngeal squamous cell carcinoma

Abstract: BACKGROUND Oropharyngeal squamous cell carcinoma (SCC) rates have been increasing significantly in recent years, despite a decreasing incidence of head and neck cancer in general. Oropharyngeal cancer has many characteristics that are distinctively different from other head and neck cancers, and thus it is important to focus specifically on cancers arising here, with the goal of improving patient outcomes. One important goal is to identify patients who are likely to fail standard therapy and who could potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 40 publications
2
51
0
1
Order By: Relevance
“…Ascertaining the origin and development of liver cancer and identification of novel targets for therapy have been the focus of recent studies regarding HCC (3)(4)(5)(6)(7). MicroRNAs (miRs) are single-stranded noncoding RNAs, containing 17-19 nucleotides, which are associated with the development and progression of tumors (8)(9)(10)(11)(12) such as oropharyngeal squamous cell carcinoma (8), non-small cell lung cancer (9), thyroid cancer (10). miR-125a has previously been reported to block the proliferation, invasion and migration of breast cancer cells (13), and was also found to be effective in preventing the invasion of ovarian cancer (14), glioma (15), lung cancer (16)(17)(18) and gastric cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…Ascertaining the origin and development of liver cancer and identification of novel targets for therapy have been the focus of recent studies regarding HCC (3)(4)(5)(6)(7). MicroRNAs (miRs) are single-stranded noncoding RNAs, containing 17-19 nucleotides, which are associated with the development and progression of tumors (8)(9)(10)(11)(12) such as oropharyngeal squamous cell carcinoma (8), non-small cell lung cancer (9), thyroid cancer (10). miR-125a has previously been reported to block the proliferation, invasion and migration of breast cancer cells (13), and was also found to be effective in preventing the invasion of ovarian cancer (14), glioma (15), lung cancer (16)(17)(18) and gastric cancer (19).…”
Section: Introductionmentioning
confidence: 99%
“…The results varied, with many miRs proposed to correlate with tumor HPV status or outcome, with few miRs found common between studies. Mir-9, 155 and 163b were in several studies found overexpressed in HPV-positive vs. HPV-negative OPSCC, while miR-31 and 193b were downregulated (68)(69)(70)(71)73). Also, a 25 miR signature discriminating HPV-positive vs. HPV-negative OPSCC was suggested, but few of the indicated miRs were common with other studies (67).…”
Section: Microrna Expression In Oropharyngeal Cancer In Relation To Hmentioning
confidence: 88%
“…MicroRNA (miR) expression in OPSCC has been mainly analyzed in normal tissue, HPV-positive vs. HPV-negative tumor status and to a lesser extent to outcome (67)(68)(69)(70)(71)(72)(73). The results varied, with many miRs proposed to correlate with tumor HPV status or outcome, with few miRs found common between studies.…”
Section: Microrna Expression In Oropharyngeal Cancer In Relation To Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Gao et al, 6 miRNAs were found to significantly correlate with prognosis: miR-142-3p, miR-146a and miR-26b over-expression were associated with improved survival, while miR-31, miR-24 and miR-193b over-expression were associated with poorer patient outcome [59]. miR-451 has also been identified as significantly over-expressed in HNSCC patients without recurrent disease [55].…”
Section: Associations With Survival and Prognosismentioning
confidence: 99%